Da ditadura à democracia: O que publicaram os jornais de São Paulo sobre a pena de morte? - Barbosa, Ana Clotilde Coutinho (2016)
The death penalty has been the focus of several studies for decades. In this sense, the present study has the aim to analyze the various discourses used by the two most important newspapers of São Paulo (Estado and Folha) to address the death penalty issue in each of the three political periods from the last fifty years of Brazilian history: Dictatorship (from 1968 to 1974), Transition from dictatorship to democracy (1987 to 1995) and the Democratic period (2005 to 2011). For that, were collected the articles from the newspapers “Estado de São Paulo” and “Folha de São Paulo” that had the words “death penalty” in their titles. In the first analysis, the material was processed by the statistical package ALCESTE in order to verify which general death penalty themes were grouped by the lexical analysis. Two analysis techniques from the ALCESTE data processing were used: the Hierarchical Sort Descending and the Factorial Analysis Correspondence. The results of the first analysis made possible the class agglutination, and they were divided into classes that contained either debate or informative articles. From the analysis held in the newspaper “Estado de São Paulo”, the following classes were found: “Debate: Life and Crime” – Class IV (47,71% of the corpus) and “Constitutional Debate” – Class II (17,47%). They stood out for being classes containing articles that enable the debate on the death penalty. On the informative side, there were the classes “Trials in Dictatorship” – Class III (13,43%) and “International News” – Class I (21, 39%). The results for the same analysis in the newspaper “Folha de São Paulo” showed the following classes: “Debate: Life and Crime” – Class II (49%) and “Constitutional Debate” – Class III (24%) which are representative of lexical elements of debate articles, and Class I – “Trials in Dictatorship” (27%) that gathered only informative news. In a second step, the material was analyzed under the technique of Content Analysis, aiming to find which were the death penalty themes most cited by the studied newspapers. As a result, the following arguments emerged: “Death penalty is efficient” versus “Death penalty is inefficient”, “Death penalty is fair” and “Death penalty is unfair” and “Lacking arguments for and against death penalty”. In fact, the debate on death penalty in Brazil was re-introduced publicly in the late 80s and this debate has extended to the present days and in every resource media. It appears that many of the arguments about the death penalty has been repeated in previous studies. It is believed that the maintenance of these discursive styles has been fed back by old discursive practices of institutions that maintain such ideas and that end up controlling the information conveyance.